2019
DOI: 10.1111/scd.12411
|View full text |Cite
|
Sign up to set email alerts
|

Prostheses satisfaction and diet of elderly wearing a single implant overdenture: A six‐month assessment

Abstract: Aims:To compare prosthesis satisfaction and nutritional intake of edentulous elderly people wearing a conventional complete denture (CD) with those wearing a single implant mandibular overdenture (SIO) after 6 months of use. Methods and results:Completely edentulous elderly patients (n = 22) were divided between a group rehabilitated with CDs in both dental arches and a group receiving a mandibular SIO with a conventional CD in the upper arch (n = 11/group). Patients completed a visual analog scale for degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Among the 9 included RCTs, 6 RCTs compared SIMO and TIMO and 3 RCTs compared SIMO and CCD 19,24‐31 . Another 8 included prospective studies were on comparison of CCD and SIMO 32‐39 . The follow‐up period varied from 3 months to 5 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 9 included RCTs, 6 RCTs compared SIMO and TIMO and 3 RCTs compared SIMO and CCD 19,24‐31 . Another 8 included prospective studies were on comparison of CCD and SIMO 32‐39 . The follow‐up period varied from 3 months to 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…There were 6 prospective studies and 4 RCTs evaluating the patient satisfaction outcome of SIMO. 26,[28][29][30]32,33,[35][36][37][38] (Tables 4 and S6) All questionnaires were completed with a maximal scale of 100 except for one study ranging from 0 to 16. 28 All prospective studies indicated that after being treated with SIMO, the edentulous patients with CCDs had a significant improvement of patient satisfaction in all comfort and functional parameters.…”
Section: Patient Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, with respect to gender, females displayed a high value of association between dentist and patient satisfaction as compared to males. Similarly, females were more likely to be satisfied with their aesthetics; however, females were less satisfied with mastication, which might be due to their need to seek treatment solely for aesthetic purposes (27)(28)(29)(30). In another study, the results showed that most patients were satisfied with their aesthetics and there was no difference between men and women; however, that study also assessed expectation levels and found that men had more expectations with their dentures as compared to females (3).…”
Section: Discussionmentioning
confidence: 96%
“…Systematic reviews (Kern, Kern, Wolfart, & Heussen, 2016; Klemetti, 2008; Roccuzzo et al., 2012) , and the consensus statement (Thomason et al., 2012) cite strong evidence that 2 implants are adequate number to retain IMO, mainly because four implants revealed only slightly reduced implant loss rates (Kern et al., 2016). That said, IMO retention by single implants installed in the mandibular midline is fairly common and reduces cost and treatment time (Carletti, Pinheiro, Meira, Amaral, & Rodrigues Garcia, 2019; Passia et al., 2017); however, MF improvements are not always observed (Amaral, Souza, Pinheiro, Campos, & Garcia, 2019) and a higher frequency of prosthesis maintenance is required (Passia, Wolfart, & Kern, 2019).…”
Section: Introductionmentioning
confidence: 99%